We couldn't even pass a resolution strongly condemning something': decision-making and procedural injustice at Rocky Flats - Milnes, Travis, author; Malin, Stephanie, advisor; Mahoney, Pat, committee member; Trumbo, Craig, committee member (Colorado State University. Libraries, 2019)
Over the course of the Rocky Flat's Nuclear Plant's operation, multiple incidents led to radioactive contamination in the surrounding environment. In 1996, state agencies agreed on a $7.3 billion remediation of the site, which was completed in 2005. On September 15, 2018, the periphery of the site was opened to the public as a Wildlife Refuge, in the center remains a space overseen by the Department of Energy. Despite remediation efforts, public opposition for both the Wildlife Refuge and the proposed roadway construction adjacent to the site remains due to concern with increased health risk for local communities. Given the history of contamination and community health response, Rocky Flats is an example of warranted environmental and procedural justice concerns. Literature indicates that procedural justice and environmental justice requires both access to information and public participation in decision-making. To examine these two elements at Rocky Flats, fifteen face-to-face interviews, participant observation of public meetings, and archival analysis was conducted. Findings indicate that Rocky Flats remains a site of environmental and procedural injustice due to the requirement of technical knowledge for public deliberation, and development of the Wildlife Refuge and the roadway despite clear public opposition. This thesis aims to contribute to environmental and procedural justice literature by examining public opposition in a post-remedial setting.
We couldn't even pass a resolution strongly condemning something: decision-making and procedural injustice at Rocky Flats
Keywords: environmental justice; nuclear contamination; Rocky Flats; health social movement; contested illness; procedural justice